Trends in the treatment of urinary stone disease in Turkey - Yildirim, Kadir; Olcucu, Mahmut Taha; Colak, Muhammed Emre (Peerj Inc, 2018)
Introduction: In this study, a survey was prepared for urologists that asked about their primary choice of treatment for urolithiasis in daily practice and their answers were evaluated. Methods: The survey was prepared on the Google Docs website and it was sent to 1,016 urologists via email with 752 confirmed deliveries. In addition to the demographic questions about each participant's age, gender, and institution, the survey presented case scenarios focusing on their preferred treatment modalities for distal ureteric, proximal ureteric, and renal calculi. The participating urologists were divided into two groups according to the frequency that they treat urolithiasis patients. Results: Of the 752 surveys delivered, 211 urologists (28.05%) responded and 204 answered all questions. According to the results, there were no significant differences between the treatment approaches and the other localizations, but there was a statistically significant difference for treatment approaches to lower pole stones between two groups. In response to the question of which stone treatment method was used less frequently, 124 (60.7%) participants answered that they used shock wave lithotripsy less in the last 10 years. Conclusion: The present study has shown that while the management of renal and ureteric calculi by Turkish urologists is highly varied, the overall treatment patterns are in accordance with the European Association of Urology guidelines. However, similar to the global trend extracorporeal shock wave lithotripsy is less preferred by Turkish urologists.
Keywords: Survey; SWL; Trend; Urolithiasis; Endourology; Stone